Zooplankton monitoring by a twin NORPAC net during the 58th Japanese Antarctic Research Expedition in austral summer 2016-2017 ... - Takahashi, Kunio; Makabe, Ryosuke; Odate, Tsuneo (Arctic Data archive System (ADS), Japan, 2018)
As part of the monitoring program of the Japanese Antarctic Research Expedition (JARE), zooplankton samplings by a NORPAC (North Pacific) standard net have been routinely carried out from JARE-14 in the 1972/73 season to estimate the mean biomass of zooplankton and time/space variation in the uppermost 150 m of the Indian Ocean sector of the Southern Ocean. Two separate monitoring surveys were completed during the JARE-58 (December 2016 to March 2017). The icebreaker Shirase has a fixed time schedule and route down 110E longitude each December and return leg along 150E longitude in March. These routine schedule of Shirase is ideal as a long-term temporal reference for monitoring work. T/V Umitakam-maru transects were also along 110E longitude in January. This report are the latest data of long-term zooplankton monitoring continued by JARE over 40 years, and can be used as time series and/or seasonal data of monitoring transects. ...